2021
DOI: 10.3390/vaccines9060682
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards the COVID-19 Vaccine and Willingness to Get Vaccinated among Healthcare Workers in French Guiana: The Influence of Geographical Origin

Abstract: Background: In the context of the global COVID-19 pandemic and the expansion of the more transmissible 20J/501Y.V3 (Gamma) variant of concern (VOC), mRNA vaccines have been made available in French Guiana, an overseas French territory in South America, from mid-January 2021. This study aimed to estimate the willingness to be vaccinated and the socio-demographic and motivational correlates among Health Care Workers (HCWs) in French Guiana. Methods: A cross-sectional survey was conducted from January 22 to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…In addition, Alvarado-Socarraset al 14 found that between 77.0% and 90.7% of physicians in Colombia accept COVID-19 vaccination. According to a study undertaken by Vignier et al, 15 65.6% of respondents reported that they were willing or had already been vaccinated against COVID-19, while 24.3% of respondents reported that they did not want to get vaccinated against COVID-19, and 11.2% were unsure. On the other hand, a study conducted in Chile by Cerda et al 26 indicated that 49% of respondents are willing to be vaccinated, while 28% were undecided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Alvarado-Socarraset al 14 found that between 77.0% and 90.7% of physicians in Colombia accept COVID-19 vaccination. According to a study undertaken by Vignier et al, 15 65.6% of respondents reported that they were willing or had already been vaccinated against COVID-19, while 24.3% of respondents reported that they did not want to get vaccinated against COVID-19, and 11.2% were unsure. On the other hand, a study conducted in Chile by Cerda et al 26 indicated that 49% of respondents are willing to be vaccinated, while 28% were undecided.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Alvarado-Socarras et al 14 found that between 77.0% and 90.7% of physicians in Colombia accept COVID-19 vaccination. According to a study undertaken by Vignier et al 15 in French Guiana, 65.6% of respondents reported that they were willing or had already been vaccinated against COVID-19, while 24.3% of respondents reported that they did not want to get vaccinated against COVID-19, and 11.2% were unsure.…”
Section: Introductionmentioning
confidence: 99%
“…Beliefs about vaccines and trust in health authorities are crucial during vaccination campaigns [ 14 ] and vaccine hesitancy has been widely documented in adult subjects [ 15 , 16 ]. This study shows for the first time that both vaccine hesitancy and refusal of vaccines against COVID-19 are very low among caregivers living in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 23 Studies have revealed that the acceptance rate of COVID-19 vaccine in the United States of America (USA) 54%, 14 France (71.6%), 27 USA (57.6%), 22 Kuwait (83%), 28 Ethiopia (72.2%), 29 Ethiopia (54.8%), 25 China (84.3%), 30 Saudi Arabia (64.9%), 31 Kenya (61.33%), 32 China (83.5%), 33 Turkey (54%), 34 UK (71.7%), 35 China (91.3%), 36 Ecuador (91%), 37 and France (65.6%). 38 …”
Section: Introductionmentioning
confidence: 99%